A pH responsive and superporous biocomposite hydrogel of Salvia spinosa polysaccharide-co-methacrylic acid for intelligent drug delivery. Issue 8 (8th February 2023) - Ali, Arshad; Haseeb, Muhammad Tahir; Hussain, Muhammad Ajaz; Tulain, Ume Ruqia; Muhammad, Gulzar; Azhar, Irfan; Hussain, Syed Zajif; Hussain, Irshad; Ahmad, Naveed
Abstract : Mucilage from seeds of Salvia spinosa (SSH; polymer) and methacrylic acid (MAA; monomer) are copolymerized to obtain a pH responsive superporous hydrogel for the controlled delivery of venlafaxine HCl. Abstract : Herein, a drug delivery system (SSH- co -MAA) based on the mucilage from seeds of Salvia spinosa (SSH; polymer) and methacrylic acid (MAA; monomer) is introduced for the controlled delivery of venlafaxine HCl using a sustainable chemical approach. The optimized conditions for the designing of the ideal formulation (M4) of SSH- co -MAA were found to be 2.5% (w/w) of SSH, 30.0% (w/w) of MAA, 0.4% (w/w) of both N, N ′-methylene-bis-acrylamide (MBA; cross-linker) and potassium persulfate (KPS; initiator). The structure characterization of SSH- co -MAA by Fourier transform infrared and solid-state CP/MAS 13 C-NMR spectroscopy has confirmed the grafting of MAA onto SSH. The thermogravimetric analysis revealed that SSH- co -MAA is a stable entity before and after loading of the venlafaxine HCl-loaded SSH- co -MAA (VSSH- co -MAA). Scanning electron microscopy images of SSH- co -MAA after swelling then freeze drying showed the superporous nature of the hydrogel. The gel fraction (%) of SSH- co -MAA depended upon concentration of SSH, MAA, and MBA. The porosity (%) was increased with the increase in the concentration of SSH and decreased with the decrease in the concentration of MAA and MBA. The swelling indices, venlafaxine HCl loading, and release (24 h at the pH of the gastrointestinal tract) from VSSH- co -MAA were found to be dependent on the pH of the swelling media and the concentration of SSH, MAA, and MBA. The release of venlafaxine HCl followed non-Fickian diffusion mechanism. Conclusively, SSH- co -MAA is a novel material for potential application in targeted drug delivery applications.